The Impact of Trump’s Policies and Rhetoric on U.S. International Relations and Domestic Politics (2016-2024) | O Impacto das Políticas e da Retórica de Trump nas Relações Internacionais e na Política Interna dos EUA (2016-2024) - Habib Badawi (Political Observer)
Donald Trump’s tenure as the 45th President of the United States from 2017 to 2021 was marked by a series of controversial policies and rhetoric that significantly impacted both the nation’s international relations and domestic political landscape. This paper provides an in-depth exploration of the multifaceted effects of Trump’s presidency on global affairs and internal political dynamics from 2016 to 2024. Through a comprehensive analysis of his foreign policy actions, economic decisions, and rhetorical strategies, the study aims to elucidate the broader implications of his leadership on the world stage and within the United States. Incorporating a rigorous review of significant policy shifts, international agreements, economic reforms, and public opinion data, the research seeks to assess the lasting influence of Trump’s tumultuous presidency on the country’s global standing and internal cohesion.